A Matemática na Produção de Jogos Digitais com Inteligência Artificial - ASSUNÇÃO, Pedro Darc da Cruz (Universidade Federal do Tocantins, 2023)
The objective of this work to list the mathematical concepts that are explored in the construction of digital games. Bibliographic research was used in a qualitative approach. The texts that served as the research database (corpus) were two books on the development of digital games by the authors: Tonéis (2015) and Buckland (2005). As a technique to analyze the data obtained deconstruction and unitarization carried out in the corpus, Discursive Textual Analysis (ATD) was used, which led us to two units of meaning: the development of digital games without Artificial Intelligence and the development of digital games with Intelligence Artificial. A dialectical movement that resulted in mathematical models that range from the use of the Pythagorean theorem to the Fuzzy set theory in the implementation of digital games. What made us conclude that the new emerging for computational creations is also the urgency of introducing Fuzzy Mathematics into the training courses that work with Mathematics.